THE EFFECT OF CARTOON SCREENING DISTRACTION TECHNIQUES ON THE ANXIETY LEVEL OF PEDIATRIC PATIENTS IN DENTAL AND ORAL HEALTH SERVICES - Culia Rahayu; Tineu Novianty Senjaya; Hadiyat Miko (JDHT Journal of Dental Hygiene and Therapy, 2023)
There are many pediatric patients who visit the Cibogo Health Center to get dental health services, but when dental services are about to be carried out, many children feel anxious and afraid when they will have their teeth examined, therefore it is important to divert attention to children to reduce excessive anxiety during dental and oral health services. The purpose of this study was to analyze the anxiety level of pediatric patients before and after showing cartoon films on the anxiety level of pediatric patients. The research method used was a pre-experimental design method with a one group pretest and posttest research design. At the beginning of the one group pretest posttest design, observations were made through the pretest first, then given treatment or intervention, then given a posttest so that you can find out the changes that occurred before and after being given treatment or intervention. The sample used in this research is Accidental Sampling.The results of the study showed that there was an effect of the distraction technique of showing cartoon films on the level of anxiety in pediatric patients. The conclusion of this study is the anxiety level of pediatric patients at the time before being given a distraction with the criteria of anxiety 36.7%, Very Anxious 23.3%; The anxiety level of pediatric patients after being given a distraction with the criteria of anxiety was 13.3%, Very anxious was not there (0%) and wilcoxon test results with a significance value of 0.014. The conclusion is that there is an influence of the distraction technique of showing cartoon films on the anxiety level of pediatric patients.